Are we reversing the trend in waste generation - Korica, Predrag (Economic and business review, 2020)
The purpose of this research is to investigate whether there is a decline in the amounts of generated municipal waste that is influenced by the changes which cannot be attributed to the changes in the socio-economic variables and can therefore be ascribed to a changing behaviour and the effectiveness of the policies implemented with the aim of preventing generation of waste. The analyses in this paper cover the data of 30 European countries in the period 2002-2015. The method applied is the panel data analysis of the data on seven socio-economic variables by using both the fixed-effect and the random-effects models. The results of our research show that if we control the model for the socio-economic variables, a decline in the amounts of generated municipal waste can be observed in the period 2011-2015, indicating certain effectiveness of the implemented policies on waste prevention in Europe.
Keywords: Evropa; komunalni odpadki; municipal waste generation; ravnanje z odpadki; socio-economic factors; varstvo okolja; waste prevention policy